Predictors of early nasal CPAP failure and effects of various intubation criteria on the rate of mechanical ventilation in preterm infants of <29 weeks gestational age. Issue 5 (30th January 2011) - Fuchs, H; Lindner, W; Leiprecht, A; Mendler, M R; Hummler, H D
Abstract : Introduction: Delivery room management using early nasal continuous positive airway pressure (nCPAP) may delay surfactant therapy. Objective: To identify factors associated with early nCPAP failure and effects of various intubation criteria on rate and time of intubation. Design: Retrospective analysis of the first 48 h in infants of 23–28 weeks gestational age (GA) treated with sustained inflations followed by early nCPAP. Results: Of 225 infants (GA 26.2±1.6 weeks) 140 (62%) could be stabilised with nCPAP in the delivery room, of whom 68 (49%; GA 26.9±1.5 weeks) succeeded on nCPAP with favourable outcome and 72 infants (51%; GA 26.3±1.4 weeks) failed nCPAP within 48 h at a median (IQR) age of 5.6 (3.3–19.3) h. History or initial blood gases were poor predictors of subsequent nCPAP failure. Intubation at fraction of inspired oxygen (FiO2 )≥0.35 versus 0.4 versus 0.45 instead of ≥0.6 would have resulted in unnecessary intubations of 16% versus 9% versus 6% of infants with nCPAP success but decreased the age at intubation of infants with nCPAP failure to 3.1 (2.2–5.2) versus 3.8 (2.5–8.7) versus 4.4 (2.7–10.9) h. Conclusions: Medical history or initial blood gas values are poor predictors of subsequent nCPAP failure. A threshold FiO2 of ≥0.35–0.45 compared to ≥0.6 for intubation would shorten the time to surfactant delivery without a relevant increase in intubation rate. An individualised approach with a trial of early nCPAP and prompt intubation and surfactant treatment at low thresholds may be the best approach in very low birthweight infants.